Efectos de la de rítmica Jaques-Dalcroze en variables psicológicas y físicas. - Treviño Flores, Elda Nelly (2018)
Propósito y Método de Estudio: Ante el exhorto de la Organización Mundial de la Salud para la implementación de intervenciones no farmacológicas y sustentables para mejorar el bienestar de los adultos mayores, el objetivo de este estudio es evaluar la eficacia de la pedagogía musical Rítmica JaquesDalcroze (RJD) en variables psicológicas y físicas en adultos mayores en una intervención de ocho sesiones semanales. Durante las sesiones las personas escuchan, sienten y expresan la música mediante la integración de movimiento corporal. Hipótesis: La RJD tiene efectos positivos en las variables de estudio. Método: diseño quasi experimental con análisis cuantitativo utilizando SPSS versión 24 con medidas pre y post y análisis cualitativo manual en una muestra de N = 60 (M = 73 años) dividida en tres grupos experimentales y un grupo control. Los instrumentos utilizados fueron versiones en español de: (a) variables psicológicas: WHOQOL-BREF, MMSE, PANAS, SDFSS-2, SFSS-2, TMT; (b) variables físicas: WHOQOL-BREF, escala de Tinetti, prueba de coordinación y ritmo, (c) entrevistas estructuradas. Los resultados muestran una diferencia positiva estadísticamente significativa en la medida post en algunos indicadores de las variables estudiadas. Por lo tanto la hipótesis de investigación es aceptada parcialmente. Contribuciones y Conclusiones: Desde la perspectiva de la psicología positiva, la Rítmica Jaques-Dalcroze es una pedagogía musical no farmacológica y sustentable que se dirije a las dimensiones cognitiva, afectiva, social y física del ser humano la cual promueve el envejecimiento saludable a través de una trayectoria óptima continua mediante el trabajo centrado en mantener la capacidad funcional e intrínseca de la persona y mejorar su bienestar subjetivo. ABSTRACT The increase of the population of older adults worldwide, challenges societies to find sustainable, non-pharmacological interventions with positive effects for this population. Studies suggest that artistic activities have positive effects in the lives of older adults. From the perspective of positive psychology, the music pedagogy Dalcroze Eurhythmics (DE) is centered on the psychological and physical domains of the human being. During DE sessions the persons listen, feel, and express music developing their innate musicality through the integration of body movements. DE sessions are divided in activities of improvisation, coordination, ear discrimination, and musical expression. Objective: to evaluate the efficacy of DE on psychological and physical variables in older adults through an eight-week intervention. Hypothesis: the music pedagogy DE has positive effects on psychological and physical variables. Materials and method: quasi-experimental design with quantitative analysis using SPSS 24 with measures pre-post, and manual qualitative analysis in a sample of N = 60 (M = 73 years) divided in three experimental groups and a control group. The instruments used were the Spanish versions of: (a) psychological variables: WHOQOL-BREF, MMSE, PANAS, SDFSS-2, SFSS-2, TMT; (b) physical variables: WHOQOL-BREF, the Tinetti test, coordination and rhythm test; (c) structured interviews. Results: the positive difference was statistically significant post-test in a few of the indicators of the variables of study; therefore, the research hyphotesis is partially accepted. Conclusions: From the perspective of positive psychology, DE is a sustainable non-pharmacological music pedagogy which addresses the cognitive, affective, social, and physical dimensions of the human being. For this reason DE can be used to promote healthy ageing through the psychological and physical variables studied related to the functional and intrinsic capacities of older adults, thus improving subjective wellbeing. Yet, further longitudinal studies are needed in this field.